EXTENSION OF VASICEK MODEL TO THE MODELLING OF INTEREST RATE - Udoye, Adaobi; Akinola, Lukman; Ogbaji, Eka (FUDMA JOURNAL OF SCIENCES, 2020)
Interest rate modelling is an interesting aspect of stochastic processes. It has been observed that interest rates fluctuates at random times, hence the need for its modelling as a stochastic process. In this paper, we apply the existing Vasicek model, ItÃ´â€™s lemma and least-square regression method in the modelling and providing dynamics for a given interest rate.